EVALUATION OF THE EFFECTIVENESS FOLIAR APPLICATION OF HUMIC ACID IN ENHANCING GROWTH AND YIELD OF SUGARCANE (Saccharum officinarum L.) VARIETIE - Abdullah, Shizar Dara; Salih, Rabar Fatah (Science Journal of University of Zakho, 2025)
Sugarcane (Saccharum officinarum L.) is a crop of significant agro-industrial value. This study aimed to evaluate the effects of foliar application of humic acid at different concentrations (0, 10, and 15 g per 4 L water) on the growth and yield performances of three sugarcane varieties (CP72-2086, CP89-2143, and CP81-325), additionally it was to ensure of growing sugarcane because for the first time it has been tested in the Erbil environment. The experiment was done in 15 April 2024, at Grdarasha Field, College of Agricultural Engineering Sciences. The results indicated that CP81-325 var. superior to other varieties for all parameters. Also, growth and yield were significantly improved in the interaction treatment (S3H1), so the maximum values of plant height, internode length and total fresh yield were (3.79m, 35.00cm and 0.88 kg cane-1), respectively. Similar result of total fresh yield (0.88 kg cane-1), was recorded by the CP89-2143 var.  when humic acid at the concentration of (15 g 4L-1 water) added to the plants, while in the control treatment (S2H0) just about (0.69 kg cane-1). Mostly, humic acid 10 g 4L-1 water showed the significant role in response for all varieties. Applying humic acid is necessary, it is not only for enhancing productivity but also for soil improvement and environment protection
Keywords: Sugarcane; Humic Acid Foliar Application; Improve Productivity; Prevent Environment Pollution